2016
DOI: 10.1097/hjh.0000000000000819
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between aortic root size and glomerular filtration rate in hypertensive patients

Abstract: Our study seems to suggest that a reduced renal function may adversely influence ARD. This may contribute to explain the enhanced cardiovascular risk associated with renal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…The first important findings of this study are that compared to the patients without DM, those with DM had lower ARD/BSA, and that significantly fewer of the patients with DM had aortic root dilatation. A previous meta-analysis of 8 studies reported that the prevalence of aortic root dilatation in patients with hypertension was around 10%, and that is was even higher in male and elderly patients [20], which is consistent with the study by Mule et al [14]. In our study, the prevalence of aortic root dilatation was higher in the patients without DM than in those with DM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The first important findings of this study are that compared to the patients without DM, those with DM had lower ARD/BSA, and that significantly fewer of the patients with DM had aortic root dilatation. A previous meta-analysis of 8 studies reported that the prevalence of aortic root dilatation in patients with hypertension was around 10%, and that is was even higher in male and elderly patients [20], which is consistent with the study by Mule et al [14]. In our study, the prevalence of aortic root dilatation was higher in the patients without DM than in those with DM.…”
Section: Discussionsupporting
confidence: 92%
“…Only a few studies have investigated the association between renal function and ARD, and the relationship between the rate in the decline of eGFR and ARD is unclear. A previous study on hypertension reported an inverse association between eGFR and ARD [14], and that albuminuria was not correlated with aortic root size [21]. Vascular calcification occurs in patients with CKD, and it is associated with arterial stiffness.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a recent study, an inverse correlation between aortic root dimension and estimated glomerular filtration rate was elucidated 4 . An enlarged aortic root, possibly indicating the occurrence of arterial ventricular remodeling, was associated with an increased risk of heart failure 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the method, AoR dilation in stage 5 was found in 39% of the patients, when using absolute measurements of the AoR, in 31% of the patients when the AoR was indexed for height, or in 18% of the patients, when using AoR normalized to BSA. 19 In another study, Kaddorauch et al 20 evaluated the effect of impaired renal function on the aortic diameter in 97 pediatric patients (mean age, 11.2 years), including patients on chronic hemodialysis or peritoneal dialysis, and in 19 KTx recipients, who were not analyzed separately. More than 80% of the pediatric patients had hypertension.…”
Section: Methodsmentioning
confidence: 99%